N-terminal BET bromodomain inhibitors disrupt a BRD4-p65 interaction and reduce inducible nitric oxide synthase transcription in pancreatic β-cells - Nord, Joshua A.; Wynia-Smith, Sarah L.; Gehant, Alyssa L.; Jones Lipinski, Rachel A.; Naatz, Aaron; Rioja, Inmaculada; Prinjha, Rab K.; Corbett, John A.; Smith, Brian C. (Frontiers in Endocrinology, 2022)
Chronic inflammation of pancreatic islets is a key driver of β-cell damage that can lead to autoreactivity and the eventual onset of autoimmune diabetes (T1D). In the islet, elevated levels of proinflammatory cytokines induce the transcription of the inducible nitric oxide synthase (iNOS) gene, NOS2, ultimately resulting in increased nitric oxide (NO). Excessive or prolonged exposure to NO causes β-cell dysfunction and failure associated with defects in mitochondrial respiration. Recent studies showed that inhibition of the bromodomain and extraterminal domain (BET) family of proteins, a druggable class of epigenetic reader proteins, prevents the onset and progression of T1D in the non-obese diabetic mouse model. We hypothesized that BET proteins co-activate transcription of cytokine-induced inflammatory gene targets in β-cells and that selective, chemotherapeutic inhibition of BET bromodomains could reduce such transcription. Here, we investigated the ability of BET bromodomain small molecule inhibitors to reduce the β-cell response to the proinflammatory cytokine interleukin 1 beta (IL-1β). BET bromodomain inhibition attenuated IL-1β-induced transcription of the inflammatory mediator NOS2 and consequent iNOS protein and NO production. Reduced NOS2 transcription is consistent with inhibition of NF-κB facilitated by disrupting the interaction of a single BET family member, BRD4, with the NF-κB subunit, p65. Using recently reported selective inhibitors of the first and second BET bromodomains, inhibition of only the first bromodomain was necessary to reduce the interaction of BRD4 with p65 in β-cells. Moreover, inhibition of the first bromodomain was sufficient to mitigate IL-1β-driven decreases in mitochondrial oxygen consumption rates and β-cell viability. By identifying a role for the interaction between BRD4 and p65 in controlling the response of β-cells to proinflammatory cytokines, we provide mechanistic information on how BET bromodomain inhibition can decrease inflammation. These studies also support the potential therapeutic application of more selective BET bromodomain inhibitors in attenuating β-cell inflammation.